2021
DOI: 10.1107/s2053230x21009675
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of acetylxylan esterase from Caldanaerobacter subterraneus subsp. tengcongensis

Abstract: The acetylxylan esterases (AXEs) classified into carbohydrate esterase family 4 (CE4) are metalloenzymes that catalyze the deacetylation of acetylated carbohydrates. AXE from Caldanaerobacter subterraneus subsp. tengcongensis (TTE0866), which belongs to CE4, is composed of three parts: a signal sequence (residues 1–22), an N-terminal region (NTR; residues 23–135) and a catalytic domain (residues 136–324). TTE0866 catalyzes the deacetylation of highly substituted cellulose acetate and is expected to be useful f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 39 publications
1
5
1
Order By: Relevance
“…The symmetric interactions at interfaces II and III promoted the rapid assembly of dimers to form crystals. Although our previous report could not clearly refer to the presence of NTR in the crystals, the present results suggest that NTR was cleaved over a long crystallization time (6 months) and then assembled and crystallized through electrostatic interactions [10]. These results suggest that the NTR functions in way to cover the molecular surface of the catalytic domain and prevent dimerization, causing the rapid formation of protein crystals.…”
Section: Structure Determination Of Ntr-truncated Mutantcontrasting
confidence: 69%
See 4 more Smart Citations
“…The symmetric interactions at interfaces II and III promoted the rapid assembly of dimers to form crystals. Although our previous report could not clearly refer to the presence of NTR in the crystals, the present results suggest that NTR was cleaved over a long crystallization time (6 months) and then assembled and crystallized through electrostatic interactions [10]. These results suggest that the NTR functions in way to cover the molecular surface of the catalytic domain and prevent dimerization, causing the rapid formation of protein crystals.…”
Section: Structure Determination Of Ntr-truncated Mutantcontrasting
confidence: 69%
“…The results showed that TTE0866 was disordered from Leu47 to Asp94 located on the NTR, which matched well with the results obtained in PONDR. The residues 23-46 were confirmed to be a highly hydrophilic region similar to the residues 47-94 by the hydropathy plot described in the previous study [10]. Thus, the majority of the NTR (72 of 113 residues, 64%) is a disordered region.…”
Section: Structural Analysis Of Ntrsupporting
confidence: 69%
See 3 more Smart Citations